A Pivotal Role for AP-1-Mediated Osteopontin Expression in the Increased Migration of Vascular Smooth Muscle Cells Stimulated With HMGB1 - Jeon, Eun Yeong; Baek, Seung Eun; Kim, Ji On; Choi, Jong Min; Jang, Eun Jeong; Kim, Chi Dae (Frontiers in Physiology, 2021)
Migration of vascular smooth muscle cells (VSMCs) plays an essential role in the development of vascular remodeling in the injured vasculatures. Previous studies have identified high-mobility group box 1 (HMGB1) as a principal effector mediating vascular remodeling, however, the mechanisms involved have not been fully elucidated. Thus, this study investigated the role of HMGB1 on VSMC migration and the underlying molecular mechanisms involved. VSMCs were ex plant cultured using rat thoracic aorta, and the cellular migration was measured using wound-healing assay. Osteopontin (OPN) mRNA and protein were determined by reverse transcription polymerase chain reaction (RT-PCR) and Western blot, respectively. The OPN promoter was cloned into pGL3-basic to generate a pLuc-OPN-2284 construct. Migration of VSMCs stimulated with HMGB1 (100 ng/ml) was markedly increased, which was significantly attenuated in cells pretreated with MPIIIB10 (100-300 ng/ml), a neutralizing monoclonal antibody for OPN as well as in cells deficient of OPN. In VSMCs stimulated with HMGB1, OPN mRNA and protein levels were significantly increased in association with an increased promotor activity of OPN gene. Putative binding sites for activator protein 1 (AP-1) and CCAAT/enhancer-binding protein beta (C/EBPβ) in the indicated promoter region were suggested by TF Search, and the HMGB1-induced expression of OPN was markedly attenuated in cells transfected with siRNA for AP-1. VSMC stimulated with HMGB1 also showed an increased expression of AP-1. Results of this study suggest a pivotal role for AP-1-induced OPN expression in VSMC migration induced by HMGB1. Thus, the AP-1-OPN signaling axis in VSMC might serve as a potential therapeutic target for vascular remodeling in the injured vasculatures.